Retronym as a Mean of Formation of New English Terms - Ossokina, D.; Murzalina, B. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
The article considers retronyms in modern English language in the sphere of electronic education. The examples of modern retronyms and the fields of their functioning are given. The author introduces such concepts as retronym, retronymia, and retronymic sentence. The paper suggests mechanisms for the formation of retronyms, as well as formulates the reasons for their appearance in modern English. The research reveals linguistic and extra linguistic factors that influence the appearance of English retronyms in the field of electronic education